2018
DOI: 10.1029/2018ms001420
|View full text |Cite
|
Sign up to set email alerts
|

A New Number Format for Ensemble Simulations

Abstract: A new number format for ensemble simulations for weather and climate predictions is presented. The new format exploits similarities between ensemble members to reduce overall data usage. Data use and movement is the most important performance bottleneck for weather and climate models on modern supercomputers. The new format can be realized on standard hardware and with standard computing languages such as Fortran. The format is tested in simulations with a shallow water model. Advantages and disadvantages are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…For weather prediction models, a natural and practical strategy is to focus on the quantitative and objective prediction skill metrics that are routinely used for model evaluation. In the studies of Ván a et al (2017), Thornes et al (2017), and Düben (2018), the skill metrics employed included the continuous ranked probability score (Hersbach, 2000), anomaly correlation coefficient (WMO, 2015), absolute error or root-mean-square error (RMSE) score (WMO, 2015), and ranked probability skill score (Christensen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For weather prediction models, a natural and practical strategy is to focus on the quantitative and objective prediction skill metrics that are routinely used for model evaluation. In the studies of Ván a et al (2017), Thornes et al (2017), and Düben (2018), the skill metrics employed included the continuous ranked probability score (Hersbach, 2000), anomaly correlation coefficient (WMO, 2015), absolute error or root-mean-square error (RMSE) score (WMO, 2015), and ranked probability skill score (Christensen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…(), Thornes et al. (), and Düben (), the skill metrics employed included the continuous ranked probability score (Hersbach, ), anomaly correlation coefficient (WMO, ), absolute error or root‐mean‐square error (RMSE) score (WMO, ), and ranked probability skill score (Christensen et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Using simplistic chaotic models, it was shown that the majority of 64 bits at double precision do not contain real information [19]. Running algorithms used for weather forecast models at precision lower than single, for example with half precision 16-bit floats, is an active field of research, but remains challenging [9,10,17,30]. Most research on reduced precision modelling for weather and climate applications makes use of software emulators [8] that provide other arithmetics than the widely supported single and double precision floats.…”
mentioning
confidence: 99%